2019
DOI: 10.1111/jfpp.14221
|View full text |Cite
|
Sign up to set email alerts
|

Water distribution of raw and heat‐induced gelation of minced pork paste prepared by soy protein isolates and carrageenan: Ingredients modify the gelation of minced pork

Abstract: Effects of soy protein isolates (SPI) and carrageenan (CAR) on water distribution of raw and heat‐induced gelation of minced pork prepared by combined soy protein isolates and carrageenan mixture were investigated using low‐field nuclear magnetic resonance. Four treatments included control, 5.7% SPI, 0.7% CAR, combined 5.7% SPI, and 0.7% CAR. Distributed exponential analysis of the T2 relaxation revealed that three water components corresponding to the three water molecule states existed during the heat‐induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Meanwhile, the free water content decreased from 4.74% to 1.61%. Interestingly, up to 0.5% CAR, the immobile water content in CAR-CSM system decreased to some extent, the free water content increased, and the bound water content remained essentially unchanged, which may be attributed to the fact that the excess CAR caused fragmentation of the gel network, and the free water was released as a result ( Gao, Xiong, & Fu, 2019 ).
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, the free water content decreased from 4.74% to 1.61%. Interestingly, up to 0.5% CAR, the immobile water content in CAR-CSM system decreased to some extent, the free water content increased, and the bound water content remained essentially unchanged, which may be attributed to the fact that the excess CAR caused fragmentation of the gel network, and the free water was released as a result ( Gao, Xiong, & Fu, 2019 ).
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…Those authors also observed that meatballs with soy flour inclusions at 10% and 15% were most acceptable (Odiase et al., 2013 ). In addition, existing studies have suggested that the addition of soy protein and carrageenan can greatly enhance the gel strength and the water retention of beef minced (Gao et al., 2019 ; Hao et al., 2016 ). However, as a potential allergen, soybean protein may risk the health of the consumers.…”
Section: Effects Of Raw Materials and Ingredients On The Quality Of B...mentioning
confidence: 99%
“…For example, some non-muscle protein ingredients are introduced into surimi systems, serving as fillers to form relatively stable gel products supported by the hydrogen bonding interactions [ 3 ]. Gao et al [ 4 ] found that the addition of soy protein benefits for the improved gel strength of the meat paste based on their inherent gelation properties. Besides, the addition of non-muscle protein can also change the gel properties of surimi products via the modulation of microstructure.…”
Section: Introductionmentioning
confidence: 99%